Potential side effects of using ammonia to inhibit bromate formation during the ozonation of drinking water. Issue 6 (19th November 2007) - Hofmann, R.; Andrews, R.C.
Abstract : This note identifies potential side effects of using ammonia to inhibit bromate formation during the ozonation of drinking water, and makes preliminary predictions of their significance. Based on kinetic calculations, it is expected that ammonia would not exert a significant ozone demand and consequently would have little impact on the ozonation process. The ammonia needed to inhibit bromate formation is also not expected to promote nitrification in distribution systems, since the ammonia would either typically be removed through breakpoint chlorination or would be used to form chloramines. However, the impact of ammonia on biologically active filters, which often follow ozonation, is more difficult to evaluate since the issue has not been directly studied, and the role of nitrogen in the biological processes in such an environment is complex. Further, if chlorine were being used for secondary disinfection, any ammonia that persisted in the treated water would exert a demand and would have to be considered.